2011
DOI: 10.3324/haematol.2011.046490
|View full text |Cite
|
Sign up to set email alerts
|

Treatment advances have not improved the early death rate in acute promyelocytic leukemia

Abstract: Early mortality in acute promyelocytic leukemia has been reported to occur in less than 10% of patients treated in clinical trials. This study reports the incidence and clinical features of acute promyelocytic leukemia patients treated at Stanford Hospital, CA, USA since March 1997, focusing on early mortality. We show that the risk of early death in acute promyelocytic leukemia patients is higher than previously reported. In a cohort of 70 patients who received induction therapy at Stanford Hospital, 19% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 22 publications
3
60
0
Order By: Relevance
“…Induction failure of patients is generally related to early mortality. Early mortality is now considered one of the most critical issues in the current treatment of patients with APL [30,31]. It indicated that current interventions to prevent early death are still not adequate.…”
Section: Discussionmentioning
confidence: 98%
“…Induction failure of patients is generally related to early mortality. Early mortality is now considered one of the most critical issues in the current treatment of patients with APL [30,31]. It indicated that current interventions to prevent early death are still not adequate.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, older age was found to be a prognostic factor of early death in all published APL series [30, [65][66][67][68].…”
Section: Early Deathmentioning
confidence: 99%
“…23 Subsequently, our findings on the early death rates have been confirmed in the large but less-detailed SEER registry, 21,59 and from a single institution study. 60 Obviously, the older patients and those with severe initial symptoms and high risk of early death did not enter the clinical studies and were not identified in the large multicenter trials. Our findings from the Swedish registry emphasize that the most important area for improved management in APL is now early detection and intensified supportive care, especially in the significant fraction of patients older than 60 years, rather than changes in consolidation treatment and maintenance.…”
Section: Apl and Early Death Ratesmentioning
confidence: 99%